Vesnice v zajetí železné opony - možnosti archeologického poznání studené války - Michal Rak; Lukáš Funk; Martin Váňa (AntropoWebzin)
The past twenty-five years have seen the development of a sub-discipline in archaeology labelled “20th Century Conflict Archaeology” around the world. The sub-discipline is focused on the remains of the military, civil, political and religious conflicts of the last century. Traces of these events are examined using an interdisciplinary approach because many different sources have been left behind to serve the researchers of this field, each of which carries unique information hardly detectable from another point of view. While the First and Second World Wars have attracted the lion’s share of attention, in recent years the efforts of researchers have turned to the Cold War and to the most famous symbol of the era—the so-called Iron Curtain, a fence of barbed wire separating the Eastern and the Western blocs. The most famous part of the curtain is the Berlin Wall. Nevertheless, research of this topic in Czech academia remains marginalized. The aim of this paper is to present how these issues are studied abroad and outline opportunities to study this in the Czech Republic. Our examples are the Iron Curtain itself and the village of Maříž, in whose history the events of the last century left an indelible mark.